Help-Seeking for Mental Health Issues in Professional Rugby League Players - Kola-Palmer, Susanna; Lewis, Kiara; Rodriguez, Alison; Kola-Palmer, Derrol (Frontiers in Psychology, 2020)
Background: Despite the prevalence and negative consequences of mental health issues among elite athletes, studies suggest many do not seek professional help. Understanding barriers and facilitators to help-seeking is imperative to reduce the burden of mental health symptoms and disorders. Aims: This study aimed to elucidate factors associated with actual help-seeking behaviour in professional rugby football league (RFL) players in England and one club in France. Design: A mixed-methods cross-sectional online survey design was used, and completed by 167 professional RFL players. Methods: The survey consisted of measures of mental health, perceived psychological stress, athletic identity, knowledge of player welfare, and actual help-seeking. Additionally, one open-ended question allowed free-text comments about barriers to help-seeking. Results: Those who had sought help reported significantly higher psychological stress compared to those who had not sought help. Help-seeking was associated with better mental health literacy and higher perceived psychological stress in a multivariate analysis. The qualitative analysis revealed a number of perceived barriers to help-seeking, of which lower mental health literacy and stigma were the most prominent. Conclusions: In one of the first studies to examine actual help-seeking behaviour, professional rugby players who had sought help for mental health and personal issues were characterised by having greater mental health literacy and experiencing greater psychological stress. Players also identified feelings of embarrassment, pride, fear and shame act as barriers to seeking help for mental health issues. These results suggest focusing on increasing mental health literacy and reducing stigma may increase help-seeking behaviour for mental health symptoms.